H∞-output regulation of linear heterogeneous multiagent systems over switching graphs - Adib Yaghmaie, Farnaz (2020)
In this paper, we analyze H∞-output regulation of linear heterogeneous multiagent systems. The agents are subject to modeled and unmodeled disturbances and communicate over a switching graph. We derive a sufficient condition that guarantees H∞ output regulation for the mentioned setup. This sufficient condition places requirements on both the single-agent systems and the switching graph. The requirement on the single-agent systems is an H∞-criterion that should be satisfied by a proper design of the controller. Meanwhile, the switching graph needs to be maximally connected. Moreover, we derive an upper bound for the overall (Formula presented.) -gain of the output synchronization error with respect to the unmodeled disturbances over a fixed communication graph. We illustrate our technical developments by a simulation example.